High densification and dielectric properties of lead-free (K0.5Na0.5)NbO3 piezoelectric ceramics with optimum excess Na2O and K2O contents. (July 2015) - Sumang, Rattiphorn; Wicheanrat, Chamaiporn; Bongkarn, Theerachai; Maensiri, Santi
Abstract: Lead-free piezoelectric ceramics based on the (K0.5 Na0.5 )NbO3 (KNN) system were prepared by the solid-state reaction method. The effects of firing temperatures and excess Na2 O and K2 O on KNN ceramics were investigated. The samples were calcined between 750 and 950 °C for 4 h and the sintering range was between 1060 and 1140 °C. Impurities phases of Nb2 O5 and K2 CO3 appeared in all sintered samples, due to evaporation of some elements during in the sintering process. The average particle size and grain size increased with increased firing temperatures. After addition of excess Na2 O and K2 O with 0, 1, 2, 3, 4, 5 and 10 wt% in the system, the impurities phase did not appear in all samples. The porous microstructure gradually decreased with increased of excess Na2 O and K2 O up to 1 wt% and then slightly increased with higher than 1 wt% of excess Na2 O and K2 O. The density and dielectric constant can be improved by adding 1 wt% of excess Na2 O and K2 O.